Juridical analysis of the crime of embezzlement by sales at CV. Syabil media telecommunications - Purba, Martinus Rambe; Hendrawati, Sulkiah; Hadi, Hadi Haerul (Journal of Law Science, 2024)
The crime of embezzlement in office is embezzlement with aggravation, which means that there are certain elements of the act that make the punishment more severe than embezzlement in its basic form as regulated in Article 374 of the Criminal Code. The formulation of the problem in this study is how the application of material criminal law to the case of embezzlement in office committed by sales, and what is the basis for the judge's consideration in imposing a prison sentence of 2 years against the perpetrator of the crime of embezzlement in office committed by sales at CV. Syabil Media Telekomunikasi in Case Study Decision Number.894/Pid.B/2023/PN SRG.This research uses normative legal research methods with a statutory approach, case approach and conceptual approach. The results showed that the application of material criminal law by the Panel of Judges against the perpetrator of the crime of embezzlement in office stated that the defendant was legally and convincingly proven guilty of committing the crime of embezzlement in office as regulated in Article 374 because the perpetrator committed the crime. The conclusion of this research is that the judge decided on a prison sentence of 2 years to the defendant for the crime of embezzlement in office based on the aggravating and mitigating circumstances revealed in the trial, and the facts revealed in the trial.